Menanamkan Pendidikan Karakter Sejak Dini dengan Pembiasaan mengucap kata kata positif sebelum masuk kelas - Subaita; Daroe Iswatiningsih (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
Early childhood education (ECE) holds a crucial role in the early development of children's character and mindset. This study examines the practice of instilling the habit of using positive language as an affirmation strategy to nurture self-confidence, optimism, and a constructive attitude among children at TK ABA 01 Batu. The approach includes daily routines such as morning affirmations, interactive and engaging teaching methods, and active collaboration with parents to create a supportive and emotionally enriching learning atmosphere. Observations indicate significant improvements in children’s self-esteem, enthusiasm for learning, and ability to form positive social interactions. Challenges such as children's limited comprehension of affirmations and maintaining consistent practice were effectively addressed through simple contextual explanations and parental reinforcement. The findings suggest that cultivating the use of positive language from an early age is a powerful yet practical approach to fostering holistic character development and emotional resilience in young learners..